Stroke technique changes during competitive swimming
Races over 200 m for backstroke, breaststroke, and butterfly, and 400 in crawlstroke at the USA Long-course Championships were analyzed. Technique changes at various stages of the races were determined. Implication: Hand velocity, distance per stroke, and angle of pitch are critical for the maintenance of technique. These features should be a major emphasis of training. The maintenance of these aspects during fatigue should result in better competitive resilience. It is not satisfactory to train swimmers in fatigue zones without stressing the maintenance of propelling efficiency. If that performance feature is allowed (trained) to become inefficient at practice, then that inefficiency will be displayed in a race. Thus, when swimmers are in training fatigue, rather than stressing working harder, the coach should stress working better (i.e., performing good stroke mechanics).